MELAYU ISLAM BERAJA: IDENTITAS NASIONAL BRUNEI DARUSSALAM - Setyadi, Maitsa Hanifa (CARITA: Jurnal Sejarah dan Budaya, 2024)
Brunei Darussalam is the only country that maintains the form of an absolute monarchy in Southeast Asia, after independence from British colonialism. This form of government cannot be separated from the strong influence of an Islamic kingdom that upholds Malay customs. This research will look at the history of the formation of Brunei Darussalam's identity, starting from the history of the state of Brunei Darussalam, the establishment of the Melayu Islam Beraja identity, to the dynamics between the government and its people. Research was carried out using historical methods consisting of data collection processes (heuristics), data validation (critic), interpretation, and historiography. The results of the research show that in the course of the country's history, it was not only Bruneian Malays or Muslims who became the people of Brunei. The state has made adjustments such as holding citizenship tests with ease for those who are Muslim. For cosmopolitan communities, this treatment may be considered discriminatory. However, this step is in fact still being implemented and has been proven to be able to maintain the stability of the country, both politically and economically.